Avaliação dos fatores de risco, evolução e frequência das infecções nas cirurgias nas cirurgias de derivação ventriculo peritoneal - Fabiana Guerra Pimenta (2015)
Surgical site infections (SSI) are the third leading cause of infectious complications associated with procedures presented in variable severities. In neurological surgeries, most SSI's occur in situations of prostheses use. Since the presence of non-biological material causes a local and transient decrease in host defense it allows microbial colonization and infection. In this situation, ventriculoperitoneal shunt (VP shunt) is the most commonly performed surgery. This study aims to determine the frequency of infectious complications and the risk factors related to VP shunt at HC-UFMG from 2007 to 2011. Four hundred thirty-eight procedures were evaluated. The average age of patients was 17.2 years old, 61.4% were men and the leading cause of hydrocephalus was congenital (210; 49%). It appears that in the group of patients aged <1 year old there was statistical significance being characterized as a possible risk factor for developing SSI (95% CI 1.8 to 6.2); (P <0.001), as well as the preoperative bath/shower as a protective factor (p = 0.002). The length of hospital stay ranged from 1 to 246 days (mean of 30.8 and a median of 17.0 days). In 80% of cases, surgical time was less than 120 minutes, and regarding the exposure system, only 18.9% did not have the system exposed during the procedure. The rate of SSI VP shunt was 18.49% (81) and 17.4% considering only the clean operations with predominance of meningitis cases (51.9%), followed by ventriculitis (34.6%), superficial infection (8.6%) and deep infections (4.9%). In the samples collected from patients with SSI, Staphylococcus epidermidis (25%) was the most frequent occurrence. When checking the time between surgery and the onset of signs and symptoms of infection, in 85.2% of the cases (69), patients presented with acute infection, that is, within three months after the procedure, and 14.8% of the cases showed subacute infection (12) between three and 12 months after the procedure. The maintenance of the system and subsequent exchange was the chosen therapy for the treatment of those VP shunt -infected. In conclusion, the rates found were above those reported and in much of the international literature, being a pediatric patient was shown as a risk factor for SSI and the preoperative bath/shower as a protective factor.